Short Term Optimal Generation Scheduling of Narmada Cascaded Hydro Electric System - Mahor, Amita; Rangnekar, Saroj (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
Generation scheduling of cascaded hydropower plants at same stream of river is imperative to harness river water energy in an optimal manner. Along with hydropower, multipurpose hydropower plants are also fulfilling irrigation requirement of nearby zones. Irrigation requirements from immediate plants, natural inflows from tributaries and evaporation losses between successive reservoirs affects water levels in both reservoirs and operating heads. In this paper all of the above factors are included in water continuity equations for optimization problem formulation of a real operated cascaded hydroelectric system located on the Narmada River in Madhya Pradesh, India. Time Varying Acceleration Coefficients PSO (TVAC_PSO) has been used to determine the optimal generation schedule of the above system. The results obtained are compared with Novel Self Adaptive Inertia Weight PSO (NSAIW_PSO), and are found to give a better solution. Key words: Hydroelectric power generation; Novel Self Adaptive Inertia Weight PSO; Linearly Decreasing Inertia Weight PSO; Time Varying Acceleration Coefficient PSO; Short term generation scheduling; Narmada River; Madya Pradesh (India) DOI: 10.3126/hn.v7i0.4241 Hydro Nepal Journal of Water, Energy and Environment Vol. 7, July, 2010 Page: 71-80 Uploaded date: 31 January, 2011